Poster 2015
DOI: 10.1136/bmjspcare-2015-000978.204
|View full text |Cite
|
Sign up to set email alerts
|

P-74 Advance care planning awareness: Using the go wish card game to assess the modern Japanese view of life and death

Abstract: BackgroundAdvance care planning (ACP) is rare in Japan. There are limited venues by which people can talk about death or terminal care.AimTo determine whether a newly translated Japanese version of the Go Wish card game was effective in identifying values of highest importance in the final stages of life.MethodsSixteen young to middle-aged community-dwelling adults (6 men; 10 women) participated in a group activity introducing a Japanese version (trial version) of the Go Wish card game. A survey assessed parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Our sampling strategy also inhibits broad generalizations to other populations; however, we would argue that the present study offers an important contribution to knowledge about the reasoning and considerations leading to prioritized EoL preferences. While the GoWish cards have been used in several recent studies of different contexts and populations ( Banner et al, 2019 ; Delgado-Guay et al, 2016 ; Glennon et al, 2019 ; Kuramoto et al, 2015 ; Zachariah, Klein, Clifton-Hawkins, Andrews, & Gross, 2015 ), we have found few other studies reporting on how GoWish items have been reasoned about and negotiated by users. The study by Lee, Hinderer, and Alexander (2018) on EoL preferences for Chinese Americans is a rare exception, also involving community-dwelling older adults, as they briefly report on how participants commented card items.…”
Section: Discussionmentioning
confidence: 91%
“…Our sampling strategy also inhibits broad generalizations to other populations; however, we would argue that the present study offers an important contribution to knowledge about the reasoning and considerations leading to prioritized EoL preferences. While the GoWish cards have been used in several recent studies of different contexts and populations ( Banner et al, 2019 ; Delgado-Guay et al, 2016 ; Glennon et al, 2019 ; Kuramoto et al, 2015 ; Zachariah, Klein, Clifton-Hawkins, Andrews, & Gross, 2015 ), we have found few other studies reporting on how GoWish items have been reasoned about and negotiated by users. The study by Lee, Hinderer, and Alexander (2018) on EoL preferences for Chinese Americans is a rare exception, also involving community-dwelling older adults, as they briefly report on how participants commented card items.…”
Section: Discussionmentioning
confidence: 91%
“…The GoWish cards have been used in research studies with community‐dwelling adults in several countries [10, 15, 27, 28] and as the DöBra cards with majority populations in Sweden [4, 9, 17, 18], however, we have seen no other studies that have reported an extensive use of wild cards as in the present study. This may be in part due to interviewers explicitly prompting interviewees about other potential preferences not covered by card items.…”
Section: Discussionmentioning
confidence: 81%
“…The card deck, which has been made publicly available, contains 37 pre-formulated statements with items that research indicated are often important at the EoL, as well as wild cards for users to formulate other, more individual preferences not covered by those statements [9]. While most research on use of the cards derives from English-speaking populations in North America [10][11][12][13], they are available in nine other languages including Swedish (www.gowish.org), with research also conducted with elderly in Japan [14]. We are aware of only one study using the cards in an Indigenous population, i.e.…”
Section: Introduction and Aimmentioning
confidence: 99%
“…The DöBra cards are a translated and adapted version of the US GoWish cards, 20 previously used in community settings to stimulate conversations about EoL issues. 21 24 The DöBra cards include 37 preformulated statements of potential importance at the EoL, for example, ‘to be free of pain’, ‘not dying alone’, and ‘to pray’; there are also wild cards for users to freely formulate any other matters of importance. Users initially sort each card statement into one of three piles according to its priority—very important, somewhat important, and less important—and then rank the 10 most important cards from 1 to 10, with the first most important.…”
Section: Introductionmentioning
confidence: 99%
“…Users initially sort each card statement into one of three piles according to its priority—very important, somewhat important, and less important—and then rank the 10 most important cards from 1 to 10, with the first most important. This procedure has been used in previous international studies, 20 , 22 , 23 , 25 and provides a basis for reflection and discussion about EoL values and preferences.…”
Section: Introductionmentioning
confidence: 99%